2022
DOI: 10.1016/j.radonc.2022.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of robustly optimised intensity modulated proton therapy for nasopharyngeal carcinoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Although the effect of variations is not known until end of treatment, the good indications of accumulated target dose coverage and robustness in our study, suggest that a relaxed threshold for adaptation can be employed. Scandurra et al [39] reported similar results regarding robustness of proton plans but for nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 70%
“…Although the effect of variations is not known until end of treatment, the good indications of accumulated target dose coverage and robustness in our study, suggest that a relaxed threshold for adaptation can be employed. Scandurra et al [39] reported similar results regarding robustness of proton plans but for nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 70%
“…Motion management strategies in PT can be divided into passive and active techniques, depending on the patient’s breathing or whether the motion and beam delivery patterns are adjusted to each other or not. Passive motion management techniques encompass the ITV or margin-based approaches, (3D/4D) robust planning, rescanning and optimisation of the delivery sequences [34] , [82] , [83] , [84] , [85] , [86] , [87] ideally followed by a robust evaluation which serves for clinical decision-making [88] , [89] , [90] . Active motion management adjusts the beam delivery to the motion pattern potentially combined with the regulation of the patient’s breathing.…”
Section: Technological Capabilities For Motion Managementmentioning
confidence: 99%
“…Significant weight loss appeared to have the largest impact on grade 2 or higher xerostomia NTCP. The authors conclude that robustly optimized IMPT plans, in combination with volumetric verification imaging and adaptive planning, provide adequate target coverage and acceptable OAR dose variation [ 94 ]. The results of this series might not be generally translatable, given the fact that NPC patients might experience less weight loss compared to other HNC locations.…”
Section: Technical Limitationsmentioning
confidence: 99%